Corporate Governance and Performance of Shariah - Compliant Companies - Mustafa Mohd Hanefah; Muhammad Iqmal Hisham Kamaruddin; Rosnia Masruki; Mohd Marzuki Ismail (IGI Global, 2024)
Handbook of Research on Theory and Practice of Global Islamic Finance (2 Volumes)